Etiology of Community Acquired Pneumonia at a Tertiary Care Hospital - Ritika Jha; Sumit Sengupta; Anshuman Mukhopadhyay; Ritam Chakraborty (The Journal of Association of Chest Physicians)
Background: Data regarding etiological profile of community acquired pneumonia are sparse, and a variation is seen in studies from different parts of India, hence underlining the need for local data for better patient management. Methods: Retrospective database analysis was done. Patients aged >18 years admitted from August 2019 to February 2020 at AMRI Hospital, Salt Lake, Kolkata, India with a diagnosis of community acquired pneumonia were included in the study. Pneumonia Severity Index and CURB 65 were used to assess the severity. Chest radiographs were thoroughly examined. Upper and lower respiratory BIOFIRE panels, sputum culture, blood culture, urinary pneumococcal antigen, and Xpert Flu were used to identify the pathogens. Outcomes were recorded. Result: No pathogen could be isolated in 30 (36.14%) cases. Viral agents were isolated in 21 (25.3%) cases. Streptococcus pneumoniae was the most common pathogen, isolated in 17 (20.48%) cases followed by Haemophilus influenzae in nine cases (10.84%), influenza virus in six cases (7.2%), Moraxella catarrhalis, rhino virus, and parainfluenza virus in five (6.02%) cases each, Staphylococcus aureus and Corona virus in four cases (4.8%), Klebsiella pneumoniae in three cases (3.61%), Mycoplasma pneumoniae in two cases (2.41%), as well as RSV, adenovirus, pseudomonas, proteus, acinetobacter, and Aspergillus fumigatus were in one (1.2%) case each. Severity of pneumonia at presentation was significantly associated with outcome. Conclusion: A total of fifty-three cases, in which a pathogen could be isolated, viral agents were isolated in 21. S. pneumoniae was the most common pathogen isolated (17 cases) followed by H. influenzae (9 cases). More than 1 pathogen was isolated in 12 cases, of which nine had one viral and one bacterial agent; S. pneumoniae being the most common bacterial co-pathogen.